Perbandingan Faktor Biomotor (V02max, Agility, Strange, Speed, Flexibility, Power) pada Atlit Cabang Olahraga Team dan Individu di Kelas Khusus Olahraga (KKO) - Iwandana, Dody Tri; Falaahudin, Ardhika; Alfia Nugroho, Wildan; Ardiansyah, Septa; Sururi, Muntaha (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
The purpose of this study was to determine the comparison of biomotor factors (VO2max, agility, strength, speed, flexibility, and power) in team and individual sports athletes in the Special Sports Class (KKO) of SMP Negeri 13 Yogyakarta. The population in this study was athletes in the special sports class (KKO) at SMP Negeri 13 Yogyakarta, totaling 120 students, using quantitative descriptive methods. The data collection technique used a physical condition test instrument with success indicators, namely being able to determine the results of the Comparison of Biomotor Factors (VO2max, Agility, Strength, Speed, Flexibility, Power) in Team and Individual Sports Athletes in the Special Sports Class (KKO) of SMP Negeri 13 Yogyakarta. The results showed that VO2Max was not significantly different between individual and team athletes, indicating that both groups had relatively similar levels of cardiorespiratory fitness; Agility between individual and team athletes also showed no significant differences, indicating similarities in fast movement and change of direction abilities. Strength: There was no significant difference in upper body muscle strength (push-ups) and abdominal muscle strength (sit-ups) between individual and team athletes, indicating that both had comparable body strength. Speed: There was no significant difference in sprint speed between individual and team athletes, indicating that both groups had relatively equivalent speed abilities. Flexibility: Individual athletes showed better flexibility than team athletes, with significant differences in the results of this flexibility test. Power: There was no significant difference in leg muscle explosive power (power) between individual and team athletes, indicating similarities in explosive ability in both groups. Conclusion: It shows that both groups of athletes (individual and team) have relatively equivalent performance in most biomotor factors, except in terms of flexibility, where individual athletes are superior. Keywords: Athletes  Biomotor Factors, Athletes, Special Sports Classes